Detector developments at DESY. (1st January 2016) - Wunderer, Cornelia B.; Allahgholi, Aschkan; Bayer, Matthias; Bianco, Laura; Correa, Jonathan; Delfs, Annette; Göttlicher, Peter; Hirsemann, Helmut; Jack, Stefanie; Klyuev, Alexander; Lange, Sabine; Marras, Alessandro; et al.
Abstract : With the increased brilliance of state‐of‐the‐art synchrotron radiation sources and the advent of free‐electron lasers (FELs) enabling revolutionary science with EUV to X‐ray photons comes an urgent need for suitable photon imaging detectors. Requirements include high frame rates, very large dynamic range, single‐photon sensitivity with low probability of false positives and (multi)‐megapixels. At DESY, one ongoing development project – in collaboration with RAL/STFC, Elettra Sincrotrone Trieste, Diamond, and Pohang Accelerator Laboratory – is the CMOS‐based soft X‐ray imager PERCIVAL. PERCIVAL is a monolithic active‐pixel sensor back‐thinned to access its primary energy range of 250 eV to 1 keV with target efficiencies above 90%. According to preliminary specifications, the roughly 10 cm × 10 cm, 3.5k × 3.7k monolithic sensor will operate at frame rates up to 120 Hz (commensurate with most FELs) and use multiple gains within 27 µm pixels to measure 1 to ∼100000 (500 eV) simultaneously arriving photons. DESY is also leading the development of the AGIPD, a high‐speed detector based on hybrid pixel technology intended for use at the European XFEL. This system is being developed in collaboration with PSI, University of Hamburg, and University of Bonn. The AGIPD allows single‐pulse imaging at 4.5 MHz frame rate into a 352‐frame buffer, with a dynamic range allowing single‐photon detection and detection of more than 10000 photons at 12.4 keV in the same image. Modules of 65k pixels each are configured to make up (multi)megapixel cameras. This review describes the AGIPD and the PERCIVAL concepts and systems, including some recent results and a summary of their current status. It also gives a short overview over other FEL‐relevant developments where the Photon Science Detector Group at DESY is involved.